Comparação da perfusão vascular folicular, luteal, uterina e perfil hormonal plasmático entre éguas jovens e idosas suplementadas ou não com L-Arginina - Resende, Hélène Lacerda de [UNESP] (2014)
Vascular perfusion of preovulatory follicles has been positively correlated with the fertility. Similarly, increased uterine vascular perfusion can result in lower rates of embryonic loss. Doppler ultrasonography allows a noninvasive and real-time hemodynamic assessment of tissues and organs. Recent studies in mares, as well as in other species, have demonstrated that the amino acid L-arginine (Arg) increases vascular perfusion of the reproductive system. The aims of this study were: a) to compare follicular, luteal and uterine vascular perfusion and hormonal profile between young and old mares; b) to evaluate the effect of supplementation of the amino acid L-arginine on the follicular, luteal and uterine vascular perfusion and on the hormonal levels of mares of different ages. For this, 10 young mares (4-10 years old) and 12 old mares (≥ 20 years) were used. Blood samples were collected daily for analysis of FSH, LH, E2 and P4 by RIA. The follicular, luteal and uterine blood flow did not differ between young and old mares in the control cycle. Plasma concentrations of FSH and LH were higher in young mares; P4 plasma concentrations were higher in older mares, and there was no difference in plasma concentrations of E2 between groups in the control cycle. Arg supplementation had a positive effect on the uterine vascularization of young mares between the D-1 and D3 and D6, and CL vascularization of the old mares in the D8. In conclusion, supplementation with Arg had no effect on most parameters assessed related with follicular, luteal and uterine vascular perfusion in both young and old mares, however a positive effect have been observed in some moments in uterine vascular perfusion of young mares and in the luteal vascular perfusion of old mares. Supplementation with Arg also had a positive effect on hormonal status of the mares